2016
DOI: 10.3109/10428194.2016.1139703
|View full text |Cite
|
Sign up to set email alerts
|

Digital PCR for quantification of recurrent and potentially actionable somatic mutations in circulating free DNA from patients with diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is an aggressive and heterogeneous malignancy harboring frequent targetable activating somatic mutations. Emerging evidence suggests that circulating cell-free DNA (cfDNA) can be used to detect somatic variants in DLBCL using Next-Generation Sequencing (NGS) experiments. In this proof-of-concept study, we chose to develop simple and valuable digital PCR (dPCR) assays for the detection of recurrent exportin-1 (XPO1) E571K, EZH2 Y641N, and MYD88 L265P mutations in DLBCL pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 39 publications
3
42
0
1
Order By: Relevance
“…To investigate the feasibility of ddPCR for MYD88 p.(L265P) detection, it was first analyzed whether results of ddPCR on FFPE material were comparable to those of former NGS analysis. As shown in Table , the results of ddPCR and NGS matched perfectly, which corresponds to previous studies that investigated correlation of NGS and ddPCR for MYD88 p.(L265P) detection or proved applicability of ddPCR for MYD88 p.(L265P) detection for several non‐Hodgkin lymphomas on FFPE material, as well as on fresh tumor tissue and in liquid biopsies (blood) …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To investigate the feasibility of ddPCR for MYD88 p.(L265P) detection, it was first analyzed whether results of ddPCR on FFPE material were comparable to those of former NGS analysis. As shown in Table , the results of ddPCR and NGS matched perfectly, which corresponds to previous studies that investigated correlation of NGS and ddPCR for MYD88 p.(L265P) detection or proved applicability of ddPCR for MYD88 p.(L265P) detection for several non‐Hodgkin lymphomas on FFPE material, as well as on fresh tumor tissue and in liquid biopsies (blood) …”
Section: Discussionsupporting
confidence: 87%
“…Considering the complication risk of a brain biopsy, mutation detection in CSF is preferred. 20,21 In addition, we have shown that ddPCR is a highly reliable and sensitive method for detection of MYD88 p.(L265P) in CSF ( Notwithstanding the previously mentioned advantages of ddPCR, one must realize that NGS is becoming more and more standard procedure for analyzing lymphomas. Also, NGS is evolving rapidly and is increasingly able to analyze small DNA concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…22 Notably, Oki et al 23 successfully detected tumor-specific immunoglobulin gene segments in blood, indicating that the principle of liquid biopsy may also be relevant for cHL patients. We recently designed a highly sensitive and specific probe-based digital polymerase chain reaction (dPCR) assay for the detection of XPO1 E571K somatic mutations in plasma cfDNA 24 that could be used as a tool to detect minimal residual disease (MRD).…”
mentioning
confidence: 99%
“…28 Beyond the studies examining ctDNA in solid tumors, there is a growing body of literature evaluating ctDNA in adult patients with hematologic malignancies. [29][30][31][32][33][34][35][36] Although ctDNA has been evaluated in the peripheral blood of children with leukemia, these assays lack the sensitivity of modern minimal residual disease assays (MRD). 37,38 In CNS tumors, detection of ctDNA in the peripheral blood is possible, but sensitivity appears to be a challenge in these patients.…”
Section: Introductionmentioning
confidence: 99%